Determinants of Household Food Security in Urban Areas - Mutiah, Sarah Ayu; Istiqomah, Istiqomah (Universitas Negeri Semarang, 2017)
Food security at household level is a very important precondition to foster the national and regional food security. Many people migrate to urban areas in the hope of improving their welfare. Generally people think that in the city there are more opportunities, but the opposite is true. The problem is more complex in the city especially for people who do not have adequate skills and education. This study aims to address whetherÂ age of household head, household size, education level of household head, income, and distribution of subsidized rice policy affect the food security of urban poor households in Purbalingga district. A hundred respondents were selected from four top villages in urban areas of Purbalingga with the highest level of poverty. Using binary logistic regression, this study finds significant positive effect of education of household head and household income and significant negative effect of household size and raskin on household food security, while age of household head has no significant effect on household food security. The results imply the need for increased awareness of family planning, education, improved skills, and increased control of the implementation of subsidized rice for the poor.